(3hSGFd GdEYdGe h GdeTcdGJ Ydi GdUYjOjf GdhWfj h GdYQHj (B:s (3GdhGbY(B, (3GdMdhd h GdJMOjGJ (B/s - (3eLehYI ef GdeDdajf s; (3HQjc(B;(3HhNHRI (B;(3bGSjejs ((3GdLRGFQ (B:s (3TQcI GdCUGdI ddfTQ ,s, 2021)
(3jCJj gPG GdcJGH djTNU hGbY GdeTcdGJ GdGLJeGYjI h jHMK aj OhQ hSGFd GdGYdGe GdJbdjOjI h GdLOjOI h cPdc GdMedGJ GdGYdGejI aj ecGaMI GdeTcdGJ GdGLJeGYjI dQUO eOi GSgGegG aj JTcjd GdhYj GdGLJeGYj HGYJHGQ Gf GdGYdGe GMO GdeaGJjM GdGSGSjI dJMbjb GdJfejI h MUhd GdJZjjQ aj GdLJeY h gPG ef NdGd YQV OQGSGJ JMdjdjI h feGPL JWHjbjI deTcdGJ GLJeGYjI jYGfj efgG GdYGde GdYQHj HUaI YGeI h GdeLJeY GdLRGFQj Ydi hLg GdNUhUs
Keywords: (3GdEYdGe h GdEJUGds; (3GdYdhe GdELJeGYjIs